Percepciones de profesionales de trabajo social sobre las condiciones laborales en Cali: años 2019-2020 - Vivian Andrea Ladino-Mosquera; Laura Sofía Chacón-Gironza (Eleuthera)
The objective of this article is to investigate the working conditions of graduate social workers from three universities in Cali, Colombia, focusing on their perceptions of their workload, salaries, contracts and life projects. The research methodology was mixed and sought the analytical integration of qualitative and quantitative data, i.e., data from the interviews and the survey were contrasted and reviewed on the basis of categories of analysis such as labor fields, job characteristics and level of job satisfaction. The results show that some elements that characterize the labor market in societies that implement neoliberal logics reproduce specific forms of hiring and, in turn, labor conditions that are detrimental to the employee. It is concluded that the logics of the current labor market influence the perceptions of these professionals about their employment.